PENGARUH KOMPETENSI DOSEN DAN MOTIVASI BELAJAR TERHADAP KEMAMPUAN ANALISIS STATISTIKA MAHASISWA FTIK IAIN KENDARI - Abdul Kadir (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2018)
This research aims to find out how lecturers’ competence and learning motivation affect the students’ statistical analysis ability. This research was carried out at FTIK IAIN Kendari academic year 2016/2017. Population and sample is focused on the 54 students who have successfully passed the statistics and research methodology course. The instruments used are tests, questionnaires and documentation study. Data analysis techniques used are descriptive and inferensial analysis after the test meets the requirements of linearity, multicollinearity, normality and autocorrelation continued with the hypothesis testing through multiple linear regression analysis and path analysis. The research results indicate that; 1) the lecturers’ competence partially affecrs the students’ inferential statistics analysis capabilities significantly, 2) the students’ learning motivation partially affects the students’ inferential statistics capability significantly, and 3) the lecturers’ competence and the students’ motivation significantly affect the students’ inferential statistics capabilities. Both of these variables contribute collectively as much as 62.2% to the students’ inferential capability, while the rest 37.8% influenced or described by other factors which are not addressed in this study.